"On Edge All the Time": Mixed-Status Households Navigating Health Care Post Arizona's Most Stringent Anti-immigrant Law - Sofía Gómez; Anna O. O'Leary (Frontiers Media S.A., 2019)
Arizona's state-level policies restricting undocumented immigrants' access to public benefits continue to have implications on mixed-status households' accessibility to care. More notably, the effects of prolonged stress, anxiety and trauma remain unaddressed whilst mental health services continue to be absent. This article examines the healthcare experiences of mixed-status households after Arizona's SB1070 ("Support Our Law Enforcement and Safe Neighborhoods Act") was passed. Arizona Senate Bill 1070 (SB1070) was state legislation empowering police to detain individuals unable to prove their citizenship upon request. Of particular interest is how households navigate accessibility to care when members have varied immigration statuses, hence, varied healthcare availability. Interviews with 43 households in Tucson, Arizona, 81% of which had at least one undocumented member, reveal barriers and promoters to care. Barriers include complexity of applications, fear and trepidation in seeking care. Promoters include discount care programs that are a vital source of care as well as discretionary practices exercised by front-line staff. Findings have implications beyond Arizona as immigrants settle in new destination states while the current Trump administration borrows from Arizona's anti-immigrant policies.